Proposed Policy for Problem Solutions and Guidelines for Improvement in 3-Year Development Plan: A Case Study of Esarn Municipal District, Buriram Province: Proposed Policy for Problem Solutions and Guidelines for Improvement in 3-Year Development Plan: A Case Study of Esarn Municipal District, Buriram Province - Jongmeesuk, Thanapat; Todsamat, Pattaraphon; Phromsathit, Sakon (RATANABUTH JOURNAL, 2023)
The objectives of this research were 1) Study the level of problem solving in the preparation of a three-year development plan. 2) Comparison of problems in preparation of three-year development plans classified by sex, age, education, occupation, length of stay in the community. and 3) to make a policy proposal, asking the organization's three-year development plan to respond to research. foot The total number of people residing in Isan Mahasarakham municipality was 18,391 people, selected from the sample group according to the formula of Taro Yamane, 391 people. The instrument used for data collection was a questionnaire. The qualitative part used in-depth interview technique for 15 people. The opinions of the sample group towards policy proposals to solve problems and ways to improve the preparation of three-year development plans were at a high level with an average of 4.14 (S.D.=0.23). To policy proposals to solve problems and ways to improve the preparation of plans classified by gender, age, education, occupation and length of residence in the community. It was found that overall and each aspect were not different. The results of the analysis of opinions on policy proposals to solve problems and ways to improve the preparation of development plans 1) The municipality has a development plan to support and increase efficiency. 2) The development of agriculture and industry is considered the heart of the people because of the occupation of the people in the area. 3) The plan must be based on good governance so that the community Access and participate in local joint development to create balance in management and fairness.